Enhancing Students’ Scientific Literacy on Environmental Pollution through Problem-Based Learning and Interactive Digital Modules - Kuswandi, Nadya Firstilia; Meriza, Nadya; Dina Maulina; Utami, Gamilla Nuri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study explores the effectiveness of the Problem-Based Learning (PBL) model supported by interactive digital modules in enhancing junior high school students’ scientific literacy, particularly in learning about environmental pollution. The study was conducted at a public junior high school in Bandar Lampung using a quasi-experimental design with a non-equivalent control group. A purposive sampling technique was employed to select participants, comprising 61 students divided into an experimental group (n = 30) and a control group (n = 31). The learning intervention in the experimental group integrated PBL strategies with interactive digital modules, while the control group received conventional instruction. Data were collected using a standardized scientific literacy test and student response questionnaires. Quantitative data were analyzed using an independent samples t-test. The results showed a statistically significant difference in scientific literacy scores between the two groups (p = 0.001), demonstrating the positive impact of the intervention. This study provides empirical evidence that the integration of PBL and digital modules offers a promising approach to improving students’ scientific literacy, especially in addressing complex and context-based environmental topics. The findings suggest that such an approach can be effectively implemented in science classrooms to foster critical thinking and environmental awareness among students.